Blunted emotion-modulated startle reflex in anorexia nervosa - Brockmeyer, Timo; Walther, Stephan; Herzog, Wolfgang; Friederich, Hans-Christoph (The international journal of eating disorders, 2019)
Objective Patients with anorexia nervosa (AN) often show difficulties in the perception, expression, and regulation of emotions and a strong avoidance of aversive feelings. According to psychobiological models, dietary restraint and accompanying weight loss may serve as a maladaptive mechanism of emotion regulation by attenuating aversive emotional states in AN, thereby contributing to the maintenance of the disorder. Method Twenty-seven women with AN and 26 age-matched healthy women were shown short film-clips to elicit fear, sadness, amusement, and neutral emotional states. Eyeblink startle response was measured by electromyography in reaction to startle-eliciting acoustic stimuli presented 12 times binaurally during each film-clip. Results As compared to healthy controls, patients with AN showed a blunted startle response to the fear- but not to the sadness-eliciting stimulus. Discussion The findings support the assumption that underweight is associated with attenuated emotional reactivity to fear-eliciting material in AN. This is in line with the hypothesis that starvation and low body weight constitute a maladaptive mechanism of emotion regulation in AN, contributing to the maintenance of the disorder.